Prevalence and characteristics of Australian women who use prayer or spiritual healing: A nationally representative cross-sectional study. (August 2016) - Rao, Angela; Hickman, Louise D.; Phillips, Jane L.; Sibbritt, David
Highlights: One in five women reported regular use of prayer or spiritual healing. Prayer or spiritual healing use is greater for women with chronic illness symptoms. Use of prayer or spiritual healing is higher in non-smokers and users of other CAM. Abstract: Objectives: To determine the prevalence and characteristics of users of prayer or spiritual healing among Australian women aged 31–36 years. Design and setting: This cross-sectional study was conducted as a part of the Australian Longitudinal Study on Women's Health (ALSWH). The sample used in the current sub-study were participants from the 'young' cohort (1973–78) (n = 8180) aged between 31 and 36 years. Main outcome measure: Use of prayer or spiritual healing Results: Prayer or spiritual healing was used on a regular basis by 20% of women aged between 31 and 36 years in 2009. Women who had symptoms of chronic illnesses (p = 0.001), women who had never smoked (p = 0.001) and women who used other forms of CAM (p < 0.001) were significantly more likely to use prayer or spiritual healing. Conclusion: A significant proportion of women use prayer or spiritual healing on a regular basis. Further research is required to better understand their rationale for using prayer or spiritual healing and its perceived impact on health related outcomes and general well-being.